Geochemical Pollution Assessment of Sediment Metal from Lower Region of the Ogun River, Nigeria - Anslem Diayi; Michael Gbadebo (Applied Environmental Research, 2014)
From depths of 0-5 cm, 5-10 cm and 10-15 cm, sediment samples were collected from three locations in the lower region of the Ogun River Basin, namely Mokoloki, Oke-Oko and Kara. The samples were obtained using Van Veen sediment grab after which they were stored in well labeled polythene bags for onward transportation to the laboratory. For pH and conductivity, samples were determined in-situ using standard methods by the American Public Health Association of 1992 while Organic Carbon was determined by the Wakley Method. The sediments were then air dried before analysis for particle size and metal concentration. Induced Couple Plasma Mass Spectrometry (ICP/MS) was used to determine metal concentrations. Data obtained were used to determine the geochemical pollution intensities for the various sediment samples. The results of physicochemical analyses revealed all sediment samples to be alkaline, while particle size analysis showed that the sediments were sandy. All metal concentrations for Cu, Pb, As, Zn, Hg, Cd, and Cr were lower than the Environment Canada Sediment Quality Guideline standards of 35.70 ppm, 35.00 ppm, 0.60 ppm, 123.00 ppm, 5.90 ppm, 0.17 ppm and 37.50 ppm, respectively. The low metal concen-trations obtained from the trace metal analyses were confirmed with an ‘unpolluted status’ obtained for all sediment samples analyzed using the geochemical accumulation index formula. Results showed that metal concentrations in these areas are low and do not pose a threat to the survival of living organisms living in sediments or the surrounding environment.